GROWTH AND YIELD EVALUATION OF SWEETPOTATO (IPOMOEA BATATAS L. (LAM)) STEM CUTTINGS STORED IN DIFFERENT PACKAGING MATERIALS - Oringo, Joan S; Alcober, Ed Allan L (Journal of Agriculture and Technology Management, 2023)
Sweetpotato cuttings are primarily the planting materials used in sweetpotato production which farmers often pack unsuitably during several days of travel and stored inappropriately on delayed planting due to inclement weather. This study was conducted to: evaluate the effects of different packaging materials in storing sweetpotato cuttings on the survival, growth, yield, and yield components of sweetpotato; identify the appropriate packaging materials in storing sweetpotato cuttings that could extend the viability of sweetpotato cuttings without significantly affecting its growth and yield; and determine the cost and return of sweetpotato production using stem cuttings stored in different packaging materials. The different packaging materials significantly affected the percentage survival of stem cuttings, the number of primary lateral vines, the number of marketable roots per plot and per hill, the number and weight of marketable roots per plot and per hectare and the total root yield (t ha-1) of sweetpotato. Cuttings wrapped in a moist newspaper gave the highest survival rating (83.33%) compared to the moist cloth (80.56%). A significantly higher number of primary lateral stems per plant (6.30) was obtained in sweetpotato from cuttings wrapped in moist cloth. The use of moist cloth obtained more marketable roots (9.32 t ha-1) and the highest total root yield (11.93 t ha-1) compared to the plants from cuttings wrapped in moist newspaper (11.57 t ha-1). The highest gross margin (PhP 142,860.00) per hectare was obtained using moist cloth as packaging material while cuttings in perforated polyethylene bags obtained the lowest gross margin (PhP 72,333.00) per hectare.